Cross-Cultural Pragmatics: An Investigation into Speech Act Realization on The Ship - Sunarlia Limbong; Novianty Palayukan; Ade Chandra; Retno Dwi Jayanti; Willyam Raimond Riwu (Universitas Cokroaminoto Palopo, 2025)
This study, titled